Finding Inner Peace: An Exploration of Forgiveness Therapy for Bullying Trauma Recovery - Yandri, Hengki; Kholidin, Farid Imam; Sujadi, Eko; Juliawati, Dosi (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2024)
This study aims to explore the effectiveness of Forgiveness Therapy in reducing the emotional pain of bullying in college students. This case study involved client "DL", a 21-year-old student who experienced bullying during Campus Orientation activities. Data were collected through Forgiveness Therapy sessions and analyzed using the Forgiveness Therapy Outcome Assessment. The results showed that the client experienced deep trauma, social anxiety, and depression due to bullying, but after undergoing Forgiveness Therapy, the client felt relief and calmness, and was free from excessive anxiety. This suggests the potential of Forgiveness Therapy in helping bullying victims recover from trauma. Further research needs to be conducted to test the effectiveness of Forgiveness Therapy on different trauma cases, such as sexual violence and domestic violence